'I am somewhat puzzled': Questions, audiences and securitization in the proscription of terrorist organizations. (April 2017) - Jarvis, Lee; Legrand, Tim
A recent wave of scholarship has drawn attention to the need for further engagement with the role of 'the audience' in securitization 'games'. This article contributes to this discussion both theoretically and empirically by exploring the types of question an audience may ask of a securitizing actor before a securitizing act meets with success or failure. To do this, it offers a discursive analysis of all 27 UK parliamentary debates on the extension of proscription powers to additional terrorist organizations between 2002 and 2014. We argue first that these debates are characterized by a wide range of questions relating to the timing, criteria, mechanics, consequences and exclusions of proscription; and second, that these questions function as demands upon the executive to variously justify, explain, clarify, elaborate and defend decisions to extend the UK's list of designated groups. Taking these questions seriously, we suggest, therefore allows insight into a variety of ways in which audiences might participate in security politics that are not adequately captured by notions of consent or resistance, or success or failure. This has empirical and theoretical value for understanding proscription, parliamentary discourse and securitization alike.